Предмет: Алгебра,
автор: ilyadmitriev0
памогите похалуйсто завтра кдр
Приложения:
Ответы
Автор ответа:
0
Преобразовывает и получаем:
2х^2-5
2х^2-5
Автор ответа:
0
(x-2)*(x+2) есть формула (a-b)*(a+b)=a^2-b^2
т.е. (x-2)*(x+2)=х^2-2^2=х^2-4
x^2-4+x^2-1=2x^2-5
т.е. (x-2)*(x+2)=х^2-2^2=х^2-4
x^2-4+x^2-1=2x^2-5
Похожие вопросы
Предмет: Қазақ тiлi,
автор: kuatkyzyaiym
Предмет: Українська мова,
автор: dgigjgj
Предмет: Алгебра,
автор: karinaagababova
Предмет: Алгебра,
автор: mitkink
Предмет: Математика,
автор: alyonadavydova